Alginate microspheres prepared by internal gelation: Development and effect on insulin stability - Silva, Catarina M. (2006)
Recombinant human insulin was encapsulated within alginate microspheres by the emulsification/internal gelation technique with the objective of preserving protein stability during encapsulation procedure. The influence of process and formulation parameters was evaluated on the morphology and encapsulation efficiency of insulin. The in vitro release of insulin from microspheres was studied under simulated gastrointestinal conditions and the in vivo activity of protein after processing was assessed by subcutaneous administration of extracted insulin from microspheres to streptozotocin-induced diabetic rats. Microspheres mean diameter, ranging from 21 to 287 [mu]m, decreased with the internal phase ratio, emulsifier concentration, mixer rotational speed and increased with alginate concentration. Insulin encapsulation efficiency, near 75%, was not affected by emulsifier concentration, mixer rotational speed and zinc/insulin hexamer molar ratio but decreased either by increasing internal phase ratio and calcium/alginate mass ratio or by decreasing acid/calcium molar ratio and alginate concentration. A high insulin release, above 75%, was obtained at pH 1.2 and under simulated intestinal pH a complete dissolution of microspheres occurred. Extracted insulin from microspheres decreased hyperglycemia of diabetic rats proving to be bioactive and showing that encapsulation in alginate microspheres using the emulsification/internal gelation is an appropriate method for protein encapsulation.